Capital Market Reaction to the Announcement of the 2024 Presidential Election Results - Rohadatul Aisy Alsen; Isti Fadah; Sumani Sumani (International Forum of Researchers and Lecturers, 2025)
The capital market becomes a place for investors to invest capital and share company for to obtain flow of funds as additional business capital. Capital market conditions are influenced by factors macro that are social, economic, and political. Political factors are very influential in trading stocks in 2024​​ that is election general (election). Research objectives This is for know whether There is difference before and after announcement results presidential election 2024 to the capital market sector energy, technology, infrastructure. Research This use approach event study and is study quantitative. Taking samples in research This use purposive sampling. The data used consists of on ten-day price closing stocks and trading volume share sector energy, infrastructure, and technology listed on the Indonesia Stock Exchange. The data analysis method used in study is a t-test difference analysis model. The results of the study This show No existence difference abnormal returns and trading volume activity before and after announcement results election president 2024 in the sector energy, technology, and infrastructure.